Ratiocination of ratios in endocrinology - Saptarshi Bhattacharya; Sunetra Mondal; Sanjay Kalra (Journal of the Pakistan Medical Association, 2024)
Endocrinology is an ever-evolving almanac of science. Precise measurement of hormones and associated analytes are necessary to practice endocrine medicine. As the endocrine system depends upon feedback and crosstalk between various glands and hormones, it makes sense to assess ratios or proportions of related hormones. We review the ratiocination, or rationale, of ratios which have diagnostic and therapeutic utility in endocrine praxis. Keywords: Feedback inhibition, hormonal assays, pituitary, thyroid, adrenal.